Bibliometric analysis of neurofeedback research from 2000 to 2022 - Siti Atiyah, Ali; Mazira, Mohamad Ghazali; Nurfaizatul Aisyah, Ab Aziz; Humaira, Nisar (NEUROTAK PUBLISHING, 2024)
The application of neurofeedback is gaining increasing interest among neuroscientists as a potential neurorehabilitation approach in cases of various neuro-related functional abnormalities. Discovering the current state of research and identifying gaps in the field of neurofeedback is an essential step in planning and mapping out future research efforts. This bibliometric analysis paper aims to identify the publications and research in neurofeedback from 2000 to 2022. A comprehensive Scopus database search was conducted using the keyword "neurofeedback" and relevant publications from 2000 to 2022 were retrieved. Bibliometric analyses were performed using the Harzing's Publish or Perish and VOSviewer software programmes. The number of retrieved documents was 1835. The number of publications has shown a steadily increasing trend since 2000, with a prominent spike in publications in 2014–2015, indicating a sudden interest in neurofeedback. Among the retrieved documents, 50.3% were related to neuroscience, 23.7% related to medicine, and 13.1% related to psychology. The main contributors to this research come from the United States (24.7%), Germany (13.7%), the United Kingdom (9.4%), and Switzerland (4.9%). Based on the network visualisation of author keywords, the most frequently occurring keywords were neurofeedback, real-time functional magnetic resonance imaging (fMRI), brain-computer interface (BCI), neuromodulation, and neurofeedback training. This bibliometric analysis presents the current status, knowledge base, and future neurofeedback study directions. These findings will benefit future researchers interested in applying neurofeedback as a potential neurorehabilitation approach for a wider population.